Pemanfaatan pelayanan Bidan di Desa di Kabupaten Muaro Jambi - ABAS, ABAS ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Background. The services of village midwives has become essential in overcoming health problems in villages. Yet, not every village midwives is willing to live at the village where they work which causes hard access for the community to get health services. From pre-observation, it was found that a part of the community distrusted the services of village midwives. The young age and unmarried status of the village midwives became some reasons of the distrust. The low support of community towards village midwives can be seen from the low coverage of first visit (K1) and fourth visit (K4) of ante natal care, and delivery in the District of Muaro Jambi in the year of 2005. Objective. The objective of this research was to know the perception of community towards the utilization of village midwives in Muaro Jambi. Methods. This research was a descriptive research, using case study design, with qualitative method. The information were collected through focus group discussion towards 48 pregnant and breast-feeding women at 4 observed villages with high and low coverage. In-depth interviews were also done towards 4 heads of village, key persons/PKK cadres, and 4 Health Center Coordinator Midwives of each observed village. The information were analyzed using thematic analysis. Result. The utilization of village midwives services was influenced by the perception of community, especially pregnant and breast-feeding women, towards the midwives services. There were several things that influenced the perception such as the ability and skill of midwives, experiences towards midwives services, midwives’ working environment, and community motivation and awareness on the needs of midwives services. Community’s financial capability, and availability of midwives also influenced the perception. Availability of midwives on-site was vital knowing that a part of the community experienced disappointment towards midwives due to their unavailability in time of needs. Principally, the community wanted their village midwives to live at their work place. There were also obstacles regarding village midwives services, such as limited medical equipments, limited stocks of medicines, inadequate infrastructures, and community’s believe on traditional birth attendance. In addition, there were also efforts from heads of village and key persons to encourage women to utilize the village midwives services. Conclusion. The perception of community towards the village midwives services was influenced by ability and skill of village midwives, working environment of the midwives, community motivation and awareness on the needs of midwives services, and the availability of village midwives at their working place.